Gülriz Uygur & Hülya Şimga (Eds.) (2018). Network to Combat Sexual Harassment and Assault at Universities: SHA Studies. Famagusta: EMU Press, 148 pages, ISBN: 978-605-95-95-18-6 - Sabancı, Tümel (My University, 2020)
[Abstract Not Available]
Keywords: Kadın Araştırmaları